Rancang Bangun Sistem Informasi Logistik - Rachmad Hidayat (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2014)
The purpose of this study to design a logistics management information system, which is able to overcome the problem of delay in sending information data items. This information system is designed to be easier to manage enterprise data, and makes all job become more effective and efficient. One of the conveniences one would be given through this information system is in search for an information about an item because all the data items will be recorded for inclusion into the database so that the information search an item will be easy and fast.